With mother on a desert island. Gender and genre at stake in Madame de Montolieu’s Le Robinson suisse (Knjiženstvo, časopis za studije književnosti, roda i kulture, 2023)
The article presents the Swiss author Isabelle de Montolieu’s reworking of Johann David Wyss’ Der schweizerische Robinson (1812/1813). The reworking consists of a translation to French in 1814, and a sequel to the work in 1824, both highly popular in the nineteenth century in France, and translated to English in both Britain and the United States. The article examines Montolieu’s negotiation of gender into the robinsonade genre, usually conceptualized as male, as well as the reception of her work. While Wyss’ work in the last decades has witnessed renewed scholarly interest, Montolieu is met with misunderstanding, reluctance, and negligence. The article discusses how gender is at stake in attempts to (re‑)canonize both Wyss’ book and the robinsonade genre at the detriment of Montolieu, and how this is related to questions of aesthetics and popularity.
Keywords: Robinsonade; gender; book history; Le Robinson suisse/The Swiss Family Robinson; Isabelle de Montolieu (1751–1832); Johann David Wyss (1743–1818)/Johann Rudolph Wyss (1782–1830)